Antidepressant-like effects of YL-IPA08, a potent ligand for the translocator protein (18 kDa) in chronically stressed rats. (February 2017) - Zhang, Li-Ming; Wang, Yu-Lu; Liu, Yan-Qin; Xue, Rui; Zhang, You-Zhi; Yang, Ri-Fang; Li, Yun-Feng
Abstract: The present study aimed to examine the molecular and cellular mechanisms underlying the antidepressant-like effect of YL-IPA08, a novel TSPO ligand designed and synthesized at our institute. We firstly used the chronic unpredictable stress (CUS) procedure of rats, a well validated stress-related animal model of depression, to further determine the antidepressant-like of YL-IPA08. And we found that YL-IPA08 caused significant suppression of inhibiting of locomotor activity, reducing the sucrose preference and increasing the latency to eat induced by CUS. In addition, YL-IPA08 treatment increased the levels of progesterone and allopregnanolone in the hippocampus and prefrontal cortex of post- CUS rats. Furthermore, long-term YL-IPA08 administration reversed dendritic shrinkage, down-regulation of neurotrophic signaling pathway within the hippocampus, as well as HPA dysfunctions simultaneously observed in the CUS rats. Collectively, the evidence presented above supports the notion that binding to TSPO and the subsequent synthesis of neurosteroid, maintenance of hippocampal morphologic and functional plasticity, and preventing HPA axis dysfunction, may account for the profound molecular and cellular mechanism underlying the antidepressant-like effect of YL-IPA08. Highlights: YL-IPA08 exerted antidepressant effects. YL-IPA08 increased neurosteroid level of post- CUS rats. YL-IPA08 reversed dendritic shrinkage of post- CUS rats. YL-IPA08 reversed the down-regulation of neurotrophic signaling of post- CUS rats. YL-IPA08 prevented HPA axis dysfunction.